(untitled) (Research, Society and Development, 2020)
To identify the perceptions of people diagnosed with depression about receiving Reiki associated with traditional treatment. Qualitative research conducted with 10 people diagnosed with depression from a Mental Health Outpatient Clinic in Southern Brazil. Data were collected through semi-structured interviews between June and July 2018 and analyzed using thematic content analysis, supported by the Unitary Human Science Theory. Two categories emerged: perceptions experienced during Reiki sessions and behavioral modifications from Reiki sessions. The participants perceived and experienced many positive aspects and changes throughout the Reiki applications. In addition, Reiki proved to be a care instrument that allowed them to expand their consciousness, thus achieving another perception of Reiki past, present and future events, indicating a better understanding of their experiences and new proposals for healthy life projects.